Climate change and tectonic implications during the Pliocene climate transition interval from lacustrine records in western Wei River Basin, central China. Issue 11 (20th December 2019) - Zhang, Tianyu; Fan, Shuanghu; Chen, Shue; Lu, Yudong
Abstract : The Earth's climate had undergone a global transition around 4–3 Ma, from warm to cool. The western Wei River Basin, its late Cenozoic tectonic evolution was mainly controlled by the expansion of the Tibetan Plateau, is affected by both Monsoon climate and Westerlies circulation. A set of lacustrine sediments between 4.2 and 3.6 Ma with clearly sedimentary rhythm are good materials for studying the palaeoclimate/palaeoenvironment changes and exploring the contained tectonic implications. We present a high‐resolution grain‐sized, magnetic susceptible, and carbonate content records from the palaeolake sediments at the global climate transition interval (4.2–3.6 Ma) in the western Wei River Basin. The abrupt changes of climate indicators at about 4.14–4.16 Ma, which is a regional response to global cooling, indicate that both westerly and monsoonal circulations were enhanced and should be attributed to global cooling rather than the uplift of TibetanPlateau. From 4.14 to 3.6 Ma, the climate represented stepwise strengthening or weakening with frequent fluctuations on the millennium scale and extreme dry events at 3.77–3.80 Ma. Combined with regional geological environment and palaeoclimate evolution data, the palaeolake that rapidly receded at 3.6 Ma provides evidence for the understanding the major climatic and environmental changes produced by the uplift of the Tibetan Plateau in western Wei River Basin and surrounding areas.